Spectrophotometric Determination of Mefenamic Acid in Pharmaceutical Preparations - Dikran, Sarmad B .; Al-Joboury, Moen I.; Mohammed, Alaa K.; Naser, Ahmed S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A simple, accurate and precise spectrophotometric method has been proposed for the determination of Mefenamic acid(MA) in dosage forms. Proposed  method based on the reaction of cited drug with 1,2-Naphthoquinone-4-Sulfonic sodium (NQS). The optimum experimental condition have been studied. Beer's Law is obeyed in the concentration range 0.5-10.0 Âµg/mL at 450nm with detection limit of 0.189Âµg/mL.  Effect of pH, reaction time, and volume of NQS on the determination of Mefenamic acid, have been examined. The proposed method has been successfully applied for the determination of  Mefenamic acid in pharmaceutical preparations.